2022
DOI: 10.1155/2022/7268273
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles Using Thespesia populnea Bark Extract for Efficient Removal of Methylene Blue (MB) Degradation via Photocatalysis with Antimicrobial Activity and for Anticancer Activity

Abstract: The green synthesis method was used to effectively fabricate Ag-NPs by using Thespesia populnea bark extract. The structural, morphological, elemental composition, and optical properties of as-synthesized Ag-NPs were characterized by powder X-ray diffraction (P-XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDAX), transmission electron microscopy (TEM), and UV-Vis spectroscopy. Their photocatalytic efficiency as a photocatalyst wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The slight line broadening of all peaks is attributed to the small size of the synthesized Ag-NPs. These results are consistent with previously reported findings . The XRD results further confirmed that the Ag-NPs are formed through the reduction of silver ions by the methanolic extract of B.…”
Section: Discussionsupporting
confidence: 93%
“…The slight line broadening of all peaks is attributed to the small size of the synthesized Ag-NPs. These results are consistent with previously reported findings . The XRD results further confirmed that the Ag-NPs are formed through the reduction of silver ions by the methanolic extract of B.…”
Section: Discussionsupporting
confidence: 93%
“…Molecules 2023, 28, x FOR PEER REVIEW 7 of 22 and sulfur confirm that the Ag-NPs were successfully capped by compounds from the EBE [37,42]. The Ag-NPs were measured using the Brunauer-Emmett-Teller (BET) method, with which their surface area and pore size distribution are precisely determined.…”
Section: Scanning Electron Microscopy Edax and Bet Analysesmentioning
confidence: 73%
“…A strong absorption peak located at 4.05 keV can be attributed to the elemental silver in the nanoparticles. In addition, the signals observed for carbon, oxygen, and sulfur confirm that the Ag-NPs were successfully capped by compounds from the EBE [37,42]. The Ag-NPs were measured using the Brunauer-Emmett-Teller (BET) method, with which their surface area and pore size distribution are precisely determined.…”
Section: Scanning Electron Microscopy Edax and Bet Analysesmentioning
confidence: 84%
See 2 more Smart Citations